When did antiquity end? : archaeological case studies in three continents : the proceedings of an International seminar held at the University of Trento on April 29-30, 2005 on late antique societies, religion, pottery and trade in Germania, northern Africa, Greece, and Asia Minor - Attoui, Redha (BAR international series ;, 2011)
Abstracts